아동의 또래간의 인기도와 대인문제해결사고와의 관계 - 양진희(Jin Hee Yang); 최기영(Kee Young Choi) (Korean Journal of child studies, 1996)
The purpose of this study was to investigate the relationship between children's popularity and Interpersonal Cognitive Problem-Solving Skill(ICPS). The subjects were 162 children(70 popular, 76 rejected, and 16 neglected children) chosen from 359 children between the age of 5 -6 and 8-9 years of age. The materials were peer nomination measures developed by Moreno(1934 ) and Interpersonal Cognitive Problem-Solving Skill produced by Park, Chan-Ok from IPCS of Spivack(1976). The data were analyzed by 3-way ANOVA popularity (3) ${×}$ age (2) ${×}$ sex (2), t-test, and $Scheff\acute{e}$ test. The results were that (1) children's popularity was significantly different by sex, (2) children's ICPS was significantly different by age for boys, (3) there was no significant difference in ICPS by popularity, and (4) there were significant differences in positive negative solution thought.